Total Water Consumption of Alfalfa as a Function of Active Soil Surface and Bioclimatic Coefficients - T. A. Pankova; A. V. Kravchuk; S. S. Orlova; O. V. Mikheeva; E. N. Mirkina (Сельскохозяйственные машины и технологии)
The paper highlights the significant impact of irrigation on crop yields, emphasizing that in the challenging climatic conditions of the dry-steppe Trans-Volga region, it is impossible to obtain a consistently high alfalfa yield without irrigation. Since irrigation presents both substantial benefits and potential drawbacks, it requires a highly skilled approach to managing irrigated lands and water resources. To estimate the total water consumption of alfalfa in the dry-steppe Trans-Volga region, it is proposed to use bioclimatic coefficients and soil surface activity indicators. (Research purpose) The study aims to determine the total water consumption of alfalfa by using bioclimatic coefficients and active soil surface values to improve the efficiency of irrigation regimes. (Materials and methods) The primary input factors influencing the total water consumption volume were analyzed. Changes in total water consumption during specific phases of alfalfa development were assessed based on evapotranspiration and the relative reserves of productive moisture, using experimental data on the crop's water consumption. (Results and discussion) The empirical coefficients representing the active surface state of alfalfa crops were determined based on the sum of average daily temperatures, calculated using Budyko-Zubenko method for estimating evaporation from the water surface. It was found that the coefficients of active surface state change significantly during plant development, increasing from 0.5 during the growth-branching period to 0.78 during branching-budding and reaching 0.99-1.0 during the budding-flowering period. (Conclusions) Curvilinear relationships between the ratio of total water consumption to evaporation and the relative reserves of productive moisture during different phases of alfalfa growth and development were experimentally established. Empirical coefficients were derived for calculating total water consumption during different periods of alfalfa vegetation grown on dark chestnut soils in the dry steppe Trans-Volga region.